Asesmen kompetensi perawatan ulkus diabetik - Dasuki Dasuki; Diah Merdekawati; Lisa Anita Sari; Rasyidah AZ; Ani Astuti; Mefrie Puspita; Rian Maylina Sari; Basok Buhari; Marthalisa Wirahandayani; Meinarisa Meinarisa (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2023)
The increasing number of diabetic ulcers in the world, Indonesia and Jambi, is an important task for nurses to intervene to prevent further complications. Health institutions, especially nursing study programs, play an active role in producing nurses who are competent in wound care. This can be achieved through learning methods. Furthermore, the assessment was carried out through the drill method (delivery of material, demonstrations and simulations) which aims to increase the competence of participants in treating diabetic ulcers. The material provided was in the form of diabetic ulcer treatment theory and continued with demonstrations of diabetic ulcer care in the form of washing and cleaning the wound. The assessment was carried out in line with the simulation carried out by the participants. The results of the activity showed that there was an increase in knowledge and skills in treating diabetic ulcers. The learning method can be applied to other teaching materials because it can increase the competency of the learning participants.